WACANA OBJEKTIFIKASI PEREMPUAN DALAM KONTEN VIRAL “UNBOXING MAHAR” DI TIKTOK - Muhammad Radja Surya Putra Budiman; Ahmad Zamzamy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid growth of social media, particularly TikTok, has turned the platform into more than a space for entertainment; it has become an arena where meanings about women are socially constructed. This phenomenon is evident in the viral “Unboxing Mahar” content, which tends to portray women as objects assessed through the material value of the dowry given to them. This study aims to examine how the discourse of female objectification is constructed within “Unboxing Mahar” content and how audiences respond to it. A qualitative approach was employed through digital discourse analysis, examining four dimensions: text, context, action and interaction, and ideology and power. Data were collected through observation of five TikTok contents and a review of relevant literature. The findings show that “Unboxing Mahar” content functions not merely as entertainment but also carries symbolic meaning that positions women as commodities valued according to material worth, a construction reinforced by patriarchal ideology and the attention-based logic of digital capitalism. Audience responses were divided between critical rejection and humorous acceptance, indicating that the discourse is actively reproduced rather than passively received. This study concludes that social media plays a significant role in shaping and disseminating discourse on female objectification, underscoring the need for critical awareness in producing and consuming digital content.